Molecular identification of dermatophytosis by polymerase chain reaction (PCR) and detection of source of infection by restricted fragment length polymorphism (RFLP) - Jha, BK; Murthy, S Mahadeva; Devi, NL (Journal of College of Medical Sciences-Nepal, 2013)
Introduction Dermatophytes are responsible for most superficial fungal infections and the estimated lifetime risk of acquiring a dermatophyte infection is between 10-20%. These fungi are mainly classified in three major genera Microsporum, Trichophyton and Epidermophyton. Materials and Methods Clinically suspected 200 cases of dermatophyte infected patients from K. R. Hospital Mysore and Mission Hospital Mysore were included in this descriptive study from January 2011 to June 2012. All the culture positive smear- 10% Potassium Hydroxide (KOH) and culture in different dermatophytic medium patients were confirmed by PCR and source of infection was detected (n=10) from PCR positive patients and (n=10) from their domestic animals by PCR-RFLP methods targeting 18S rDNA regions of fungi. Results Out of 200 clinically suspected cases KOH mount was positive in 143 (71.5%) cases and culture was positive in 132(66%) cases. The isolates belonged to three genera and eight species as T.mentagrophytes 52(39.4%), T.rubrum 30(22.7%), T.violacium 18(13.6%), T.verrucosum 11(8.3%), E.floccosum 10(7.6%), M.canis 6(4.5%), T.tonsurans 03(2.3%) and T.schollenii 2(1.5%). To identify the source of infection 10 animals ,one each from the houses of 10 patients who were PCR positive were also subjected to PCR and RFLP. The animals and the patients were found to be infected by same organisms T.verrucosum .This indicates that T.verrucosum infection is from animal source. Conclusion Dermatophytic infections are more common infectious disease. Preliminary diagnosis of dermatophytosis can be done by KOH mount and culture, which takes longer time to report and cannot differentiate at the genus and species level. Results indicate that PCR-RFLP may be considered as gold standard for the diagnosis and confirmation of source of infection of dermatophytosis and can aid the clinician in initiating prompt and appropriate antifungal therapy. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 7-15 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8694